Poročilo 6. evropskega simpozija znanosti in raziskovanja v judu in 5. znanstvenega in strokovnega kongresa o judu - Šimenko, Jožef (Šport (Ljubljana), 2019)
This year the 6th European Judo Research and Science Symposium and the 5th Scientific and Professional Conference on Judo: Applied Science in Judo was held between 12 and 14 June in Poreč, Croatia. The conference lasted three days and was organised in the framework of the 6th European Judo Festival, in co-organisation with the Faculty of Kinesiology of the University of Zagreb, the Croatian Judo Federation and the European Judo Union (EJU), under the watchful eye of Jane Bridge, Chair of the Organisation Committee and Vice-President of the EJU, as well as Prof. Dr Hrvoje Sertić, Head of the Organisation Committee.
Keywords: conference; judo; kongres; simpozij; sport; symposium; šport